Ultrasonic Foetal Weight Estimation at Term in Bangladeshi Women - A Comparative Study of Eight Formulae - Mazhur, Syed Iqbal; Hossain, Ahmed; Afroz, Laila; Chowdhury, Shiuly; Amin, Md. Nurul (Ibrahim Cardiac Medical Journal, 2013)
Ibrahim Cardiac Medical Journal 2011; 1(2): 29-34 DOI: http://dx.doi.org/10.3329/icmj.v1i2.13549